1334. Outcomes Among Influenza and SARS-CoV-2 Infection in Hospitalized Adults Age ≥ 50 Years and with Underlying Chronic Obstructive Pulmonary Disease (COPD) or Congestive Heart Failure (CHF). (4th December 2021) - Taylor, Megan; Tippett, Ashley; Hussaini, Laila; Salazar, Luis; Ciric, Caroline; Reese, Olivia; Bristow, Laurel; Patel, Vikash; Li, Wensheng; Hsiao, Hui-mien; Stephens, Kathy; Gibson, Theda; et al.
Abstract: Background: A significant burden of disease exists for adults infected with influenza (flu) and SARS-CoV-2, which causes COVID-19. However, data are limited comparing outcomes between hospitalized adults infected with these viruses. Methods: Over the course of 3 consecutive winter respiratory viral seasons, adults ≥ 50 years of age admitted with acute respiratory tract infections (ARI) and adults of any age with COPD or CHF-related admissions were enrolled from 2 Atlanta area hospitals. For the 2018-19 and 2019-20 seasons, participants were approached in the hospital. If the participant enrolled, nasopharyngeal (NP) and oropharyngeal (OP) swabs were collected and tested using BioFire® FilmArray® respiratory panel. Due to the COVID-19 pandemic in 2020-21 and limitations involving participant contact, only NP standard of care (SOC) swabs were collected. A comprehensive medical chart review was completed for each subject which encompassed data on their hospitalization, past medical history, and vaccination history. Co-infected patients were excluded from the analyses. Results: Of the eligible participants, 118 were flu positive (three RSV-influenza co-infections were excluded) and 527 were COVID-19 positive. Median age was lower for the flu cohort at 62 (IQR 56-71) than those with COVID-19 (67, IQR 59-77) (p < 0.0001). Length of stay (LOS) was shorter in flu-infected patients (median 3 d, IQR 2-6), but was longer for COVID-19 patients (median 5 d, IQR 3-10). ICU admission occurred in 20% of those with flu, and among those admitted to the ICU mechanical ventilation (MV) occurred in 12.5%. ICU admission and MV was significantly higher for those with COVID-19, with 28% of patients admitted to the ICU and 47% of those requiring MV. Among patients with COVID-19, 8.9% died. This was significantly higher than that of flu (3.4%) (p=0.008). Hospital discharge occurred more frequently to a nursing home or LTCF with COVID-19 (10.3%) than with flu (0%) (p< 0.0001). Table 1. Breakdown of age, hospitalization course, and discharge disposition for participants diagnosed with influenza or COVID-19 during hospitalization. Conclusion: COVID-19 resulted in a longer hospital admission, a greater chance of ICU admission and MV as compared to flu. Additionally, COVID-19 participants had a high rate of discharge to a nursing home/LTCF and a significantly higher risk of death. While the clinical course was not as severe as COVID-19, influenza contributed a significant burden. Disclosures: David L. Swerdlow, MD, Pfizer Vaccines (Employee) Robin Hubler, MS, Pfizer Inc. (Employee) Christina A. Rostad, MD, BioFire Inc, GSK, MedImmune, Micron, Janssen, Merck, Moderna, Novavax, PaxVax, Pfizer, Regeneron, Sanofi-Pasteur. (Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support)Meissa Vaccines (Other Financial or Material Support, Co-inventor of patented RSV vaccine technology unrelated to this manuscript, which has been licensed to Meissa Vaccines, Inc.) Larry Anderson, MD, ADVI (Consultant)Bavarian Nordic (Consultant)Novavax (Consultant)Phizer (Grant/Research Support, Scientific Research Study Investigator)Sciogen (Research Grant or Support) Nadine Rouphael, MD, pfizer, sanofi, lily, quidel, merck (Grant/Research Support) Nadine Rouphael, MD, Lilly (Individual(s) Involved: Self): Emory Study PI, Grant/Research Support; Merck (Individual(s) Involved: Self): Emory study PI, Grant/Research Support; Pfizer: I conduct as co-PI the RSV PFIZER study at Emory, Research Grant; Pfizer (Individual(s) Involved: Self): Grant/Research Support, I conduct as co-PI the RSV PFIZER study at Emory; Quidel (Individual(s) Involved: Self): Emory Study PI, Grant/Research Support; Sanofi Pasteur (Individual(s) Involved: Self): Chair phase 3 COVID vaccine, Grant/Research Support Evan J. Anderson, MD, GSK (Scientific Research Study Investigator)Janssen (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member)Kentucky Bioprocessing, Inc (Advisor or Review Panel member)MedImmune (Scientific Research Study Investigator)Medscape (Consultant)Merck (Scientific Research Study Investigator)Micron (Scientific Research Study Investigator)PaxVax (Scientific Research Study Investigator)Pfizer (Consultant, Grant/Research Support, Scientific Research Study Investigator)Regeneron (Scientific Research Study Investigator)Sanofi Pasteur (Consultant, Scientific Research Study Investigator)